Using multimodal pedagogies in writing centres to improve student writing - Archer, Arlene (Stellenbosch Papers in Linguistics Plus, 2017)
This paper focuses on the affordances of multimodal pedagogies in writing centre environments to improve student writing. Writing centres have the potential to function as change agents, contributing towards changing the dominant attitudes to language and texts. Multimodal pedagogies encourage the use of a range of modes (such as talk, writing, music and images) and a range of resources (including multilingual, experiential, embodied and technology-enriched resources). This paper explores how consultants and students use a range of modes and ensembles of modes to develop thinking and learning in a multilingual and diverse higher education context. The dual role of consultants, being both ‘reproducers’ and ‘interrogators’ of academic discourse, is touched upon, and the importance of ‘recognising’ and drawing on the ‘brought-along’ resources in the training of consultants is highlighted. The unique nature of one-on-one consultations in the tertiary environment is explored, as well as the ways in which this pedagogical space can be enhanced through the use of multimodal pedagogies. To this end, the paper examines talk as an important mode in improving writing. It also interrogates working on the screen versus the page, the affordances of mind mapping, and the balancing of creativity and constraints in the writing consultation. The aim is to theorise a multimodal approach to improving student writing through the examination of practice. The contention is that multimodal pedagogies can acknowledge consultants and students as agentive, resourceful and creative meaning-makers. This is particularly relevant in a context in which autonomous and decontextualised models of student support persist and students continue to be constructed as ‘lacking’ in resources.